Ascorbic acid modulates cell migration in differentiated HL‐60 cells and peripheral blood leukocytes. Issue 8 (8th May 2015) - Schwager, Joseph; Bompard, Albine; Weber, Peter; Raederstorff, Daniel
<x xml:space="preserve">Abstract</x> Scope The impact of L‐ascorbic acid (L‐AA) on the chemokinesis (CK) and chemotaxis (CT) of HL‐60 cells and polymorphonuclear cells (PMN) was investigated. Methods and results HL‐60 cells were differentiated with DMSO, retinoic acid (RA), vitamin D, or L‐AA. Chemokinesis and chemotaxis of differentiated HL‐cells were assayed. Vitamin D3‐treated HL‐60 cells (dHL‐60vitD3 cells) and RA‐treated cells (dHL‐60RA cells) acquired monocyte/macrophage‐like and neutrophil‐like phenotypes, respectively. DMSO induced the differentiation of an intermediate phenotype (dHL‐60DMSO cells), whereas L‐AA downregulated neutrophil markers (dHL‐60L‐AA cells). dHL‐60DMSO cells had increased CK and potent CT in gradients of IL‐8 and N‐formyl‐L‐methionyl‐L‐leucyl‐L‐phenylalanine (fMLP). dHL‐60RA cells and dHL‐60L‐AA cells migrated less toward IL‐8 and fMLP; dHL‐60vitD3 cells preferably responded to fMLP. L‐AA enhanced CK of dHL‐60DMSO cells and was a weak chemo‐attractant. In human leukocytes, IL‐8 and fMLP triggered receptor‐mediated chemotaxis. CXCR2 and fMLPR were downregulated by IL‐8 and fMLP, respectively. L‐AA stimulated chemotaxis although significantly less than IL‐8 and fMLP. IL‐8 targeted chemotaxis was enhanced both in HL‐60 cells and leukocytes when cells were incubated with L‐AA. Conclusion L‐AA modulated chemokinesis and had significant chemo‐attractant properties, which were independent on fMLP or IL‐8 receptors. The results suggest that L‐AA improves leukocyte function in innate immune responses.